Security Issues Cloud computing Storage (International Journal of Engineering and Computer Science, 2017)
Cloud computing uses the internet and central remote servers to maintain data and applications. It allows consumers and businesses to use applications without installation and access their personal files at any computer with internet access. This technology allows for much more efficient computing by centralizing data storage, processing and bandwidth. The appearance of cloud computing has made a tremendous impact on the Information Technology (IT) industry over the past few years. Recently IT industry needs Cloud computing services to provide best opportunities to real world. Cloud computing is in initial stages, with many issues still to be addressed. Security is one of the major issues which hamper the growth of cloud. The idea of handing over important data to another company is worrisome; such that the consumers need to be vigilant in understanding the risks of data breaches in this new environment. The objective of this paper is to introduce a detailed analysis of the cloud computing security issues and challenges focusing on the cloud computing types and the service delivery types..